DESIGN AND MANUFACTURE OF SKATEBOARD FROM BANANA STEM - Zulfikar, Achmad Jusuf; Umroh, Bobby; Siahaan, Muhammad Yusuf Rahmansyah (JMEMME (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY), 2019)
A skateboard is a small piece of wood shaped like a surfboard with four wheels attached to it that is used to glide on a certain track. In general, this tool is made using wood material taken from nature and vulnerable to environmental damage issues. In this research, the waste of banana stems will be processed into the main raw material for skateboarding. The type of material chosen is the type of composite material with banana stem waste selected as reinforcement and polyester resin as the matrix material. The purpose of this research is to design and manufacture a skateboard made of composite fiber reinforced banana stem fibers and to test its flexural strength to obtain the characteristics of the material formed. The design was carried out with the help of the 2007 version of Autocad software by following commercial skateboard standards.  Flexural testing was carried out at the Impact and Fracture Research Center laboratory, Faculty of Engineering, University of North Sumatra. Static static testing of polymer composite board specimens from banana stems obtained the average value data for the composition of 5% banana stems is 9.81 MPa, for the composition of 10% banana stems an average of 13.60 MPa, and composition of 15% banana stems the average is 27.20 MPa. 2. The analysis shows that the best composition is 15% of banana stems, with an average flexural strength value of 27.20 MPa. Therefore, the composition used in this study is the composition of 15% reinforcement of banana stems.